Uptake of interferon‐free DAA therapy among HCV‐infected decompensated cirrhosis patients and evidence for decreased mortality. Issue 9 (8th July 2021) - McDonald, Scott A.; Barclay, Stephen T.; Innes, Hamish A.; Fraser, Andrew; Hayes, Peter C.; Bathgate, Andrew; Dillon, John F.; Went, April; Goldberg, David J.; Hutchinson, Sharon J.
Abstract: Interferon‐free DAA therapies have recently been licensed for patients infected with hepatitis C virus (HCV) who have decompensated cirrhosis (DC). Our aim was to describe factors associated with uptake of IFN‐free DAAs in DC patients and to compare mortality risk and hospital admission rates between pre‐DAA and DAA eras. This observational study used record‐linkage between Scotland's HCV Clinical Database and national inpatient hospitalization and mortality registers. For the DAA uptake analysis, the study population ( n = 297) was restricted to patients alive on 1 November 2014, and Cox regression was used to estimate uptake associated with various covariates. For the Cox regression of mortality comparing pre‐DAA and DAA eras, the study population ( n = 624) comprised those diagnosed with DC in 2005–2018; follow‐up was censored at two years. DAA uptake was 63% overall and was significantly higher for treatment‐experienced patients (adjusted hazard ratio (aHR) = 1.64, 95% CI:1.14–2.34), genotype 1 vs. other genotypes (aHR = 1.55. 95% CI:1.15–2.10) and lower for persons diagnosed with DC pre‐2014 (0.47, 95% CI:0.33–0.68) and in Greater Glasgow (0.64, 95% CI:0.47–0.88). The intention‐to‐treat SVR rate was 89% (95% CI:83–93%). All‐cause and liver‐related mortality risk were significantly reduced among patients diagnosed with DC in the DAA era (November 2014–December 2018) compared with the pre‐DAA era (2005–October 2014) (aHRs of 0.68, 95% CI:0.49–0.93; 0.69, 95% CI:0.50–0.95, respectively); in contrast, hospital admission rates were higher in the DAA era (aRR = 1.14, 95% CI:1.04–1.26). The majority of HCV‐infected DC patients engaged with specialist services can be treated with IFN‐free DAAs. Improved survival among patients diagnosed with DC in the DAA era supports the beneficial impact of IFN‐free therapies among those with advanced liver disease.